Analisis Kesediaan Membayar Konsumen Terhadap Produk Sayur Organik di Kota Semarang - Banjarnahor, Asri Ulina; Setiadi, Agus (JURNAL LITBANG PROVINSI JAWA TENGAH, 2024)
Organic vegetable products have a relatively high selling value compared to inorganic vegetables, so the price factor is one of the reasons consumers consider organic vegetable products to be expensive food products. This study aims to describe consumer characteristics, analyze the maximum average WTP value of consumers who are willing to pay more for various organic vegetable product commodities and analyze what factors influence consumers' willingness to pay (WTP) for various organic vegetable product commodities in Semarang City. This research was carried out in 2 modern market locations in the city of Semarang with 100 respondents selected using the method accidental sampling and quota sampling. Data were analyzed using descriptive analysis to describe consumer characteristics, analysis contingent valuation methode (CVM) to calculate the maximum average value willingness to pay (WTP) and logistic regression analysis to analyze the factors that affect the value of WTP. The results of the study show that the majority of consumers are women, aged 41-50 years, last year's education is Bachelor's Degree, the number of family members is 4 people and income is Rp. 3,000,000 - Rp. 5,999,999. As many as 82% are willing to pay more with an increase of 8.15% to 9.34%. Factors of age, education level, number of family members, income, product prices and product quality simultaneously have an influence on consumers' willingness to pay for organic vegetable products. Meanwhile, partially income and product prices affect the willingness to pay for organic vegetable product consumers.